HOW ADVERTISING INFLUENCES YOUR CHOICES AND PURCHASING BEHAVIOUR WHILE SELECTING TOOTHPASTE - Trivedi, Himanshu; Gupta, N. D.; Bey, Afshan; Sharma, Vivek Kumar; Khan, Saif; Kirmani, Mahira (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
From television to wall murals, advertising is digital, ubiquitous and a powerful force shaping attitudes and behaviour in today's world. Owing to the rising consumer demands across products and services; the upsurge in competition across markets and companies vying for larger market share, advertisements, more precisely manipulative advertisements have become prevalent and the only means of generating revenues for companies that influence in ways we don't even realise. Keywords: Advertising, Purchasing, Advertising Standards Authority, Toothpaste